Integration of Urban Farming into City Infrastructure Development (Universitas Indonesia, 2022)
The ability to respond to the need for food is threatened by the scarcity of urban farmers (UF) in the elevation of the urban population. This shows that the availability of food is a cultivated land function, indicating that agriculture is only a mirage when sites are unavailable for farming. Irrespective of these conditions, the sustainability of food production within the city spaces is still the complimentary urban infrastructure enhancing the movement of goods and farmers. Therefore, this study aims to determine the patterns of integrating urban farming into city infrastructure development. In this case, a mixed methods approach was used, with a sample of 236 UF obtained across five local government areas (LGA) of Ibadan metropolis, Nigeria, due to the land availability that ranked first in the urban agriculture (UA) location within the city. Based on interviews with selected farmers and literature reviews, many UF preferred to have their farmlands located along the road for ease of mobility and access. The results showed that old age limited farming travel distance, with several cases of farm produce theft, subsequently detected. To solve these issues, land allocation and water infrastructure provision including irrigation kits were needed for the enhancement of UA and UF, respectively. In addition, comprehensive plans integrating UF infrastructure spaces were suggested.